2020
DOI: 10.1111/jonm.12934
|View full text |Cite
|
Sign up to set email alerts
|

Nurses’ emotions on care relationship: A qualitative study

Abstract: Aims: To describe nurses' experiences regarding the care relationship built with medical-surgical patients in acute hospitalization units and the association with their clinical practice. Background: Nurses' commitment to care and their relationships as well are the core of quality of care. Nurses consider that the emotional commitment is essential to the profession, thus accepting to be exposed to emotional distress. Methods: In-depth interviews were conducted to explore the experience of 23 nurses from seven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 58 publications
0
19
0
Order By: Relevance
“…76 From a nursing perspective, organisational and working environments and conditions also influence therapeutic relationships. [77][78][79] Another important feature of the patient-nurse relationship found in the literature is patient intimacy and confidentiality. Barrio-Cantalejo acknowledges that health-related relationships are based on the recognition of the right of patients to participate in health-related decisions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…76 From a nursing perspective, organisational and working environments and conditions also influence therapeutic relationships. [77][78][79] Another important feature of the patient-nurse relationship found in the literature is patient intimacy and confidentiality. Barrio-Cantalejo acknowledges that health-related relationships are based on the recognition of the right of patients to participate in health-related decisions.…”
Section: Discussionmentioning
confidence: 99%
“…76 From a nursing perspective, organisational and working environments and conditions also influence therapeutic relationships. 7779…”
Section: Discussionmentioning
confidence: 99%
“…While these findings do not reflect exploration of nurse satisfaction, other studies show that nurses are dissatisfied when they have to ration care due to lack of resources (Hegney et al., 2019). Thus, nurses' awareness of their missed care is likely a cause of frustration, dissatisfaction and emotional effects (Font‐Jimenez et al, 2019) much of which can serve to further affect care, including potentiating missed care (Aiken et al., 2012). A recent study identified that about one‐third of the nursing staff was not satisfied with their work environment, where 17% have no confidence in the field of management and the lack of support from nursing leadership was a cause for the omission of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The erosion in care is due in part to the increasing burden on nurses that not only translates into ‘more patients to take care of’, but also in emotional exhaustion, increased professional responsibility (Font‐Jimenez et al, 2019; Jacob, Mckenna, & D'Amore, 2015) and coping with ethical dilemmas on a daily basis (Suhonen & Scott, 2018). Aiken et al (2018) concluded that missed nursing care is more frequent where patient satisfaction is lower and is statistically negatively associated with outcomes on satisfaction (Aiken et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation